War and world politics. dimensions of the hegemony of the united states (2007)
Analysts should avoid the retrospective illusion of believing that the US hegemony, as a trend and a firmly entrenched practice occurred during the Independence or a little later (with the Monroe Doctrine). In fact, the onset of hegemony took place during the last decades of the XIXth century and strengthened during the following century, particularly because of the European decline. Moreover, the period following 09/11 has been a very crucial one, with the emergence of a new foreign policy that combines a large element of the doctrine of intervention, with the ancient just-war doctrine, a difficulty to take into account the change in the art of war, and the forgetfulness of the classical terms of the diplomatic and strategic behavior. The successive years will reveal if the eruption of Condoleeza Rice’s “Transformational Diplomacy” represents a real epoch-making turning point.